Amizade e a virtualização das relações humanas na sociedade contemporânea: reflexões a partir de Zygmunt Bauman - Silva, Rafael Bianchi; Carvalho, Alonso Bezerra de [UNESP] (My University, 2014)
This article analyzes the human bonds in the context of contemporary society from the work of the polish sociologist Zygmunt Bauman. Taking as starting point the bond of friendship and relational virtualization process motivated by the development of new technologies, it was observed the occurrence in the present world an affective-relational impoverishment. As an alternative to this, it is argued the exercise of building and maintenance of dense bonds that provide an alternative to the bind model of momentary satisfaction, this time marks. Finally, it is indicated that the discussion of friendship necessarily imply on the problematization of contemporary ethics which will provide the foundation for building a new affective political.

Este artigo faz uma análise dos vínculos humanos no contexto da sociedade contemporânea a partir da obra do sociólogo polonês Zygmunt Bauman. Tomando como ponto de partida a ligação da amizade e o processo de virtualização relacional movido pelo desenvolvimento de novas tecnologias, observou-se a ocorrência no mundo atual de um empobrecimento afetivo-relacional. Como alternativa a este, defende-se o exercício de construção e manutenção de laços densos que conferem alternativa ao modelo vincular de satisfação urgente e momentânea, marca do tempo presente. Por fim, indica-se que o debate da amizade implica necessariamente na problematização da ética contemporânea o que fornecerá as bases para a construção de uma nova política afetiva.
Friendship and human relations virtualization in contemporary society: reflections from Zygmunt Bauman
Keywords: Friendship; Contemporary society; Zygmunt bauman; Amizade; Contemporaneidade; Zygmunt bauman